Break Binge Eating: Reach, engagement, and user profile of an Internet‐based psychoeducational and self‐help platform for eating disorders. Issue 10 (10th August 2020) - Linardon, Jake; Rosato, John; Messer, Mariel
Abstract: Objectives: Internet‐based psychoeducational and self‐help platforms hold promise for alleviating existing help‐seeking barriers and addressing the unmet needs of people with eating disorders (EDs). In this paper, we report data related to the reach, engagement, and visitor profile of Break Binge Eating, an online platform designed to provide evidence‐based information and self‐help strategies for people at all stages of an ED . Method: Two sources of data were presented: (a) usage data from platform visitors generated through Google Analytics; and (b) characteristics of a sample of platform visitors ( n = 786). Results: In 13 months, approximately 46, 311 unique users worldwide have accessed this platform, with usage rates rapidly increasing each month. Most visitors came from organic searches (when ED‐related information is directly searched in a browser). Self‐help content was the most accessed material, and 81% of the sample stated that their reason for accessing the platform was to get help. Sample visitors were highly symptomatic; 52% met criteria resembling a threshold ED and 87% engaged in at least one ED behavior in the past month. Across different symptomatic subgroups, ∼50% were unsure whether they needed help, ∼80% were not receiving any help, and ∼75% were highly concerned with their symptoms. Conclusion: This online platform has broad reach and is engaging its intended audience. It is an aim of this platform to improve mental health literacy, facilitate symptom recognition and improvement, and alleviate help‐seeking barriers. Evaluating whether this platform is achieving its intended aims in a randomized controlled trial is the next step.